Nitrate ammonification by Nautilia profundicola AmH: experimental evidence consistent with a free hydroxylamine intermediate - Hanson, Thomas E.; Campbell, Barbara J.; Kalis, Katie M.; Campbell, Mark A.; Klotz, Martin G. (Frontiers in Microbiology, 2013)
The process of nitrate reduction via nitrite controls the fate and bioavailability of mineral nitrogen within ecosystems; i.e. whether it is retained as ammonium (ammonification) or lost as nitrous oxide or dinitrogen (denitrification). Here, we present experimental evidence for a novel pathway of microbial nitrate reduction, the reverse hydroxylamine:ubiquinone reductase module (reverse-HURM) pathway. Instead of a classical ammonia-forming nitrite reductase that performs a 6 electron-transfer process, the pathway is thought to employ two catalytic redox modules operating in sequence: the reverse-HURM reducing nitrite to hydroxylamine followed by a hydroxylamine reductase that converts hydroxylamine to ammonium. Experiments were performed on Nautilia profundicola strain AmH, whose genome sequence led to the reverse-HURM pathway proposal. N. profundicola produced ammonium from nitrate, which was assimilated into biomass. Furthermore, genes encoding the catalysts of the reverse-HURM pathway were preferentially expressed during growth of N. profundicola on nitrate as an electron acceptor relative to cultures grown on polysulfide as an electron acceptor. Finally, nitrate-grown cells of N. profundicola were able to rapidly and stoichiometrically convert high concentrations of hydroxylamine to ammonium in resting cell assays. These experiments are consistent with the reverse-HURM pathway and a free hydroxylamine intermediate, but could not definitively exclude direct nitrite reduction to ammonium by the reverse-HURM with hydroxylamine as an off-pathway product. N. profundicola and related organisms are models for a new pathway of nitrate ammonification that may have global impact due to the wide distribution of these organisms in hypoxic environments and symbiotic or pathogenic associations with animal hosts.